Management of Large‐Volume Subperiosteal Abscesses of the Orbit: Medical vs Surgical Outcomes. (29th August 2017) - Nation, Javan; Lopez, Alexis; Grover, Nancy; Carvalho, Daniela; Vinocur, Daniel; Jiang, Wen
Abstract : Objectives: To compare clinical variables and outcomes for children with subperiosteal abscesses of the orbit (SPAO) managed medically vs surgically to identify clinical prognosticators. Study Design: Case series with chart review. Setting: Tertiary children's academic institution. Subjects and Methods: The study included 48 children between the age of 1 month and 14 years, with SPAO from 2003 to 2013. Variables included age, sex, physical examination findings, laboratory results, computed tomography (CT) findings, hospital length of stay, length of antibiotic therapy, and placement of a peripherally inserted central catheter (PICC). Intended methods for comparison were the Student t test for continuous variables and Fisher's exact test for categorical variables, and a forward stepwise multiple logistic regression. Results: Thirty‐two (67%) children were successfully treated with antibiotic therapy only, and 16 (33%) required surgery. Abscess volume, abscess width, and the presence of gaze restriction were statistically different between the 2 groups. A multivariate analysis found abscess volume as the only predictor for surgical intervention. A subgroup analysis including only patients with an abscess volume of ≥500 mm 3 (n = 26) was performed. Eleven patients were treated medically and 15 treated surgically, with the medical group having longer hospital stays ( P =. 048), duration of antibiotic therapy ( P =. 035), and higher incidence of PICC placement ( P =. 005). Conclusions: This is the first study to report that abscess volume has clinical implications, as children with SPAO volume ≥500 mm 3 treated medically have longer inpatient admissions, antibiotic therapy durations, and PICC placement. When children present with an abscess ≥500 mm 3, early surgical intervention should be strongly considered, even in the absence of other surgical criteria, to shorten duration of hospitalization and accelerate clinical improvement.